2020
DOI: 10.1016/j.ijheatmasstransfer.2019.119177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotation on forced convection in wavy wall channels

Abstract: In this paper, flow field and heat transfer performance in stationary and rotating wavy channels with different shapes were numerically investigated. Three different geometries were generated through three different values of phase-shift angles of = 0, 90 and 180 degrees between ∅ the two opposite wavy walls. A cell-centred finite-volume technique was employed to solve the three-dimensional governing equations based on the SIMPLE algorithm technique. Besides, the Menter k-SST turbulence model was used to simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Heidary et al [9] numerically studied the heat transfer and flow field in a nanofluid wavy channel and showed that the heat transfer in the channels could be enhanced by 50% with adding nanoparticles and usage wavy horizontal walls. Al-Zurfi et al [26] numerically investigated the flow field and heat transfer performance in fixed and rotating wave channels with different shapes. They found that as the rotation velocity increased, the lower wall heat transfer coefficient increased significantly, while the upper wall heat transfer coefficient increased slightly.…”
Section: Introductionmentioning
confidence: 99%
“…Heidary et al [9] numerically studied the heat transfer and flow field in a nanofluid wavy channel and showed that the heat transfer in the channels could be enhanced by 50% with adding nanoparticles and usage wavy horizontal walls. Al-Zurfi et al [26] numerically investigated the flow field and heat transfer performance in fixed and rotating wave channels with different shapes. They found that as the rotation velocity increased, the lower wall heat transfer coefficient increased significantly, while the upper wall heat transfer coefficient increased slightly.…”
Section: Introductionmentioning
confidence: 99%
“…The early experimental and theoretical investigations related to the forced convective flow through wavy channels have been investigated by Rush et al (1999) and Wang and Chen (2002), respectively. Recently, several studies investigated the forced convective flow through corrugated channels (Al-Zurfi et al , 2020; Alsabery et al , 2021; Aminian et al , 2020; Shahsavar et al , 2021; Mehta and Pati, 2020a, 2020b, 2021b, 2021c, 2021d; Mehta et al , 2022a, 2022b; Aldor et al , 2022; Bayer et al , 2022; Khoshvaght-Aliabadi et al , 2022; Pourhammati and Hossainpour, 2022; Yoon et al , 2022). Tiwari and Moharana (2020) analyzed the conjugate forced convective flow through wavy and raccoon channels and observed a higher performance factor for the raccoon microchannel than the wavy and straight ones.…”
Section: Introductionmentioning
confidence: 99%
“…Tiwari and Moharana (2020) analyzed the conjugate forced convective flow through wavy and raccoon channels and observed a higher performance factor for the raccoon microchannel than the wavy and straight ones. Al-Zurfi et al (2020) studied the effect of rotation on the heat transfer characteristics in wavy channels and observed that rotational speed enhances the heat transfer. Recently, Alsabery et al (2021) studied the impact of nanofluid on the forced convective heat transfer using the particle tracking model and observed that as the size of the recirculation zone increases, nanoparticles are propelled away from the wall towards the channel core.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the trapezoid shape suggests a high Nusselt number. As for the relationship between the Reynolds number and the Nusselt number, it was studied by Al-Zurfi et al [29]. He employed a wavy channel with a phase angle of =0-180 and a range of Re=1000-10000.…”
Section: Introductionmentioning
confidence: 99%